Ikhtiar and Tawakkul in the Qur’an: An Exegetical Study of Shaykh Nawawi al-Bantani’s Marah Labid - Alfin FIkri; Munandar (Journal of Indonesian Islamic Studies, 2026)
This study examines ikhtiar (human effort) and tawakkul (reliance on Allah) in the Qur’an through Nawawi al-Bantani’s Marah Labid. It addresses the persistent tendency to separate active effort from spiritual surrender, which may produce either excessive self-reliance or passive fatalism. The study employed qualitative library research using thematic exegesis supported by tahlili analysis of Surah al-Ra‘d [13]: 11, Surah Ali ‘Imran [3]: 159, and Surah al-Talaq [65]: 3. Marah Labid served as the primary source, while classical and contemporary exegetical, theological, and relevant scholarly works provided secondary data. The data were analyzed descriptively and interpretively by identifying key meanings, comparing related interpretations, and synthesizing their theological implications. The findings demonstrate that Nawawi al-Bantani presents ikhtiar and tawakkul as complementary principles. Ikhtiar requires moral reform, careful planning, consultation, and the use of lawful means, whereas tawakkul directs the heart to rely fully on Allah after earnest effort. Human action therefore operates within the law of causality, while its final outcome remains subject to divine will and measure. This integration rejects both anthropocentric self-sufficiency and religious fatalism and provides an ethical foundation for responsibility, optimism, patience, spiritual resilience, and a balanced Muslim work ethic in contemporary life.